HUBUNGAN KUALITAS HIDUP DENGAN DIABETES MELITUS TIPE 2 - Tambunan, Nur Lela E.; Siahaan, Jekson Martiar; Simanjuntak , Salomo G. U. (Universitas Methodist Indonesia, 2021)
Background: Diabetes mellitus type 2 is a disease that cannot be cured but controlled so that it greatly affects health conditions and affects the quality of life for sufferers. Quality of life is a form of problem that occurs in various aspects of the sufferer's life, such as physical well-being, well-being, and emotional or social well-being. The gap between desire or hope and the ability to make changes in oneself. Methods: The research method used is Literature Review, using secondary data. The data were collected using documentation techniques, the research journals used were 9 journals with inclusion criteria published in the last 5 years, journals used in Indonesian and English with the research subjects of patients with diagnosis of type 2 diabetes, and full text publication. Conclusion: There is a close relationship between physical health, psychological, social support, environment and there is also a demographic relationship such as age, education level, economic status. However, for sociodemographics, sex was not related.